Effectiveness Of Giving Water Boiled From Binahong Leaves (Anredera Cordifolia) With Hypertension In The Elderly In Dusun II Helvetia Village Medan, 2015 - Tri Maya Sari (Journal Analytica Islamica, 2022)
Background: Hypertension is one of the main factors in the occurrence of cardiovascular disease and is one of the most important global health burdens because cardiovascular cases are one of the highest contributors to death in the world, including in Indonesia. Hypertension treatment can be done pharmacologically and non-pharmacologically. One of the non-pharmacological treatments and complementary therapies is boiled water from binahong leaves (anredera cordifolia) which contains high levels of flavonoids which can lower blood pressure. The aim of this study was to determine the frequency distribution of blood pressure before and after being given boiled water from binahong leaves (anredera cordifolia) to the elderly in Hamlet II, Helvetia Village. This research is quantitative research, using a quasi experiment (quasi experiment). The population in this study were all elderly people with hypertension in Hamlet II, Helvetia Village. Sampling used total sampling, namely with a sample of 40 elderly people. Blood pressure was measured before giving boiled water from binahong leaves (anredera cordifolia) for 7 days, then measured again. The percentage of changes in blood pressure before and after the binahong leaf boiled water therapy for systole was 151.55 to 93.5 while for diastole it was 94.33 to 86.80, which means there was a decrease in blood pressure in systole and diastole. The results of data analysis using the paired sample T-test in systole and diastole showed a P value = 0.000, which means a P value = <0.05, meaning that there is effectiveness of boiled water therapy from binahong leaves (anredera cordifolia) in reducing blood pressure in hypertensive patients. It is hoped that elderly people with hypertension can lower blood pressure by consuming binahong boiled water regularly.